Faktor-Faktor yang Memengaruhi Kejadian Hiperemesis Gravidarum pada Ibu Hamiltirmester I di UPTD Puskesmas Perawatan Lawe Sumur Kabupaten Aceh Tenggara Tahun 2023 - Serli Yusida; Ester Simanullang; Febriana Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Hyperemesis gravidarum is a condition in which pregnant women experience excessive nausea and vomiting which interferes with daily activities and even results in dehydration. The aim of this research was to determine the factors that influence the incidence of Hyperemesis Gravidarum in 1st trimester pregnant women in the Lawe Sumur Nursing Community Health Center Area, Southeast Aceh Regency in 2023. This type of research is an analytical survey with the population being all pregnant women who visited Antenatal Care at the Lawe Sumur Care Community Health Center, Southeast Aceh Regency in October 2022-March 2023. The sampling technique used was probability sampling and the sampling technique used was accidental sampling. In conclusion, it was found that there was a relationship between maternal age and hyperemesis gravidarum, p value 0.007. There was a relationship between parity and hyperemesis gravidarum with a p value of 0.002 and a relationship between work and hyperemesis gravidarum, p value 0.000 at the Lawe Sumur Care Health Center, Southeast Aceh Regency. Suggestions from the results of this research can be used as input in order to improve services, especially in providing information about hyperemesis gravidarum in pregnant women and also in developing knowledge about factors related to hyperemesis gravidarum.